Scientific-academic narcissism a new phenomenon in academic settings - Kiarash Ghadimi (Tehran University of Medical Sciences, 2020)
Narcissism is a type of personality disorder in which a person considers himself great and important and exaggeratedly feels capable and worthy. One of the places in which this disorder can occur is at the university level. The symptoms of this type of disorder can be seen in some faculty members and it seems that these people also have some kind of scientific-academic narcissism disorder. In this type of narcissism, the person has a sense of overconfidence and is fascinated by power and dominance, becomes disinterested in others, demands the attention of others, and believes that he deserves special attention. At the scientific and academic level, these people try to promote themselves in various ways and by abusing students (using their ability to write essays and making them do research with threats and intimidation). These people often claim to be superior in terms of scientific literacy and have a high IQ, and constantly slander their colleagues and criticize their performance unfairly. It is necessary that while preventing them from holding any managerial positions, they should also be evaluated through academic counseling centers and, if necessary, be cured through informing colleagues and family.